Diagnostic and Prognostic Roles of C-Reactive Protein in Childhood Pneumonia (Community Based Medical Journal, 2024)
A hospital-based, case-control study was conducted in the Department of Pediatrics in Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between February and September of 2013, to determine the role of CRP for the diagnosis of pneumonia as well as treatment response of pneumonia. A total of 180 children with pneumonia were enrolled – 90 as case (group A) and another 90 having ARI other than pneumonia as control (group B), based on specific inclusion and exclusion criteria. Necessary information was collected by detailed history taking, clinical examination and close follow-up in the hospital, by using a pre-designed data sheet. The mean±SD age of the participants as case (group A) and control (group B) were 8.53±10.24 and 6.68±3.59 respectively (P>0.05). Male children were 66(73.3%) and 68(75.6%), while female children were 24(26.7%) and 22(24.4%) in group A and group B respectively (P>0.05). In two groups, the mean CRP before treatment were 48.80±32.4 and 3.60±1.30 respectively; the difference was statistically significant (P7 days. Among the responders, CRP was significantly reduced after treatment (P0.05). Hence, we suggest that measuring CRP to see the antibiotic response in childhood pneumonia is helpful.  CBMJ 2024 January: vol. 13 no. 01 P: 46-52